Analysis of RRI Makassar Broadcasting Communication Strategy in Education of the Public and Increasing the Interest of New Voters - Saputra, Irsan; Sukmarini, Andi Vita; Sonni, Alem Febri (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
The 2024 presidential election will be held simultaneously throughout Indonesia, RRI Makassar as a public broadcasting institution has the responsibility to convey this information to the public. This study aims to determine the communication strategy used by RRI Makassar in educating the public and increasing the interest of new voters in the 2024 Election, as well as exploring the obstacles and supporting factors faced by RRI Makassar in implementing this strategy. This study refers to qualitative methodology and a case study approach. Empirical data were obtained from semi-structured in-depth interviews, supported by observations and literature reviews and previous research. The Grounded theory approach was used for data analysis. The main findings of this study found that the use of multiplatform in communication enabled RRI to reach a wider and more diverse segment of society, as well as increasing the effectiveness of message delivery and showed that RRI Makassar's strategy was largely successful. Presenting credible sources, such as representatives from the KPU and Bawaslu, during these events contributed significantly to the perceived success of the strategy. The study highlighted that more than 60% of the targeted audience consisted of first-time voters. The researcher also emphasized the importance of a tailored communication strategy to meet their needs. Future studies are expected to explore the long-term impact of this communication strategy on voter behavior and engagement.